2020
DOI: 10.1038/s41436-020-0750-4
|View full text |Cite|
|
Sign up to set email alerts
|

An approach to integrating exome sequencing for fetal structural anomalies into clinical practice

Abstract: Purpose: We investigated the diagnostic and clinical performance of trio exome sequencing (ES) in parent-fetus trios where the fetus had sonographic abnormalities but normal karyotype, microarray and, in some cases, normal gene-specific sequencing.Methods: ES was performed from DNA of 102 anomalous fetuses and from peripheral blood from their parents. Parents provided consent for the return of diagnostic results in the fetus, medically actionable findings in the parents, and identification as carrier couple fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 22 publications
5
74
0
Order By: Relevance
“…The FSA trios came from two sources: 1) 135 trios were prospectively recruited from Columbia University (88 trios were directly derived from previously published CMA and WES studies from this site 15,22 and 47 were unique to this study), and 2) 40 trios were prospectively recruited from the University of North Carolina (UNC) Chapel Hill Prenatal Diagnosis Program. 23,24 When possible, FSA cases were pre-screened for absence of a P/LP variant from CMA (n=171; 97.7%) and karyotype (n=155; 88.6%). Each FSA was reviewed by a board-certified perinatologist and assigned to one of eleven phenotype categories (Table S2) to assist in classifying cases as having a single congenital anomaly or MCAs.…”
Section: Subject Ascertainment and Phenotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The FSA trios came from two sources: 1) 135 trios were prospectively recruited from Columbia University (88 trios were directly derived from previously published CMA and WES studies from this site 15,22 and 47 were unique to this study), and 2) 40 trios were prospectively recruited from the University of North Carolina (UNC) Chapel Hill Prenatal Diagnosis Program. 23,24 When possible, FSA cases were pre-screened for absence of a P/LP variant from CMA (n=171; 97.7%) and karyotype (n=155; 88.6%). Each FSA was reviewed by a board-certified perinatologist and assigned to one of eleven phenotype categories (Table S2) to assist in classifying cases as having a single congenital anomaly or MCAs.…”
Section: Subject Ascertainment and Phenotypingmentioning
confidence: 99%
“…Interestingly, the missense variant in this compound heterozygous pair was originally identified by WES, and due to the specificity of the gene-disease association, the laboratory manually reviewed the WES read depth profile across this gene and identified the duplication, which was later confirmed with fluorescence in situ hybridization. 24 While WGS discovered both variants in a single test, the challenges of predicting the functional impact of in-frame IEDs resulted in a classification of VUS for the DYNC2H1 exonic duplication, despite the strong likelihood that these variants represent the molecular diagnosis for this case based on the specificity of the phenotype, the robust gene-disease assocation, and the limited number of genes associated with short-rib thoracic dysplasia. [40][41][42][43] Similar to the sequence variant guidelines, 32 future CNV recommendations could consider including additional mechanisms to increase classifications of CNVs, particularly IEDs, that are proven to be in trans with a P/LP variant.…”
Section: Application Of Wgs In Diagnostic Testing Of Fsasmentioning
confidence: 99%
“…33 More recently published data evaluating an approach to integrating ES for fetal structural anomalies into clinical practice, also noted the highest yields of pathological variants associated with cardiac and central nervous system, renal, skeletal anomalies, as well as hydrops fetalis and arthrogryposis. [34][35][36] The NHS England (Genomics) are developing testing criteria based on ultrasound to guide discussions around suitability for prospective prenatal ES ( Figure 2). It should also be recognised that mutations in the same gene can cause different prenatal and postnatal phenotypes and may differ with the same underlying genetic pathological variant.…”
Section: Fetal Phenotypementioning
confidence: 99%
“…Prenatal TAT therefore can be prioritised when there is a need to obtain a result by a specific gestation time and some centres have achieved this within an average of 14 days (range 7-38 days). [34][35][36] A recent small retrospective study from the Netherlands indicated that prenatal ES aided parental decision-making (including decisions on late termination of pregnancy) and aided prenatal/neonatal clinical pathways. Again, on average, TAT was possible within 21 days.…”
Section: Clinical Pathway 'Turnaround Time'mentioning
confidence: 99%
“… 22 25 Previous studies of pES indicate that results can impact decision-making about continuation or termination, pre- or postnatal medical management, delivery planning, recurrence risk counseling, reproductive planning, and parental medical management. 8 10 , 13 , 18 , 20 , 26 …”
Section: Introductionmentioning
confidence: 99%